DEPICTION OF AFRICAN-AMERICAN CULTURE THROUGH JAZZ MUSIC IN DISNEY ANIMATED MOVIES: A COMPARATIVE STUDY - Aisyah, Shania (Universitas Pakuan, 2024)
Over the years of making animated movies, Disney has produced movies about the life of African-Americans, namely The Princess and The Frog (2009) and Soul (2020). As one of the greatest African-American cultural legacy, jazz music’s elements can be found in these movies. The objective of this paper is to find the intrinsic elements where both movies inserted jazz’s elements as the cultural representation of African-American. By using the qualitative method and comparative literature to conduct the analysis, this paper compares how both movies include jazz and African-Americans to showcase the cultural representation. The results show that both movies have different way on depicting jazz through the intrinsic elements. The Princess and The Frog depicts jazz as a culture through its settings, while Soul through its characters, mainly the protagonist.